Plasmodium knowlesi and Wuchereria bancrofti: Their Vectors and Challenges for the Future - Vythilingam, Indra (Frontiers in Physiology, 2012)
Malaria and filariasis still continue to pose public health problems in developing countries of the tropics. Although plans are ongoing for the elimination of both these parasitic vector borne diseases, we are now faced with a daunting challenge as we have a fifth species, Plasmodium knowlesi a simian malaria parasite affecting humans. Similarly in peninsular Malaysia, filariasis was mainly due to Brugia malayi, however, we now see cases of W. bancrofti in immigrant workers coming into the country. Work is on going to eliminate malaria and filariasis from the country. In order to be successful we need to revamp our control measures. Thus this paper attempts to review the vectors of malaria and filariasis in Southeast Asia with special emphasis on P. knowlesi and W. bancrofti and their control strategies.